Pengaruh Kompetensi Dan Self-Efficacy Terhadap Pengembangan Karir Perawat Di Pusat Kanker Nasonal Rumah Sakit Kanker “Dharmais” Jakarta - Tuti Syafaatinur; Tulus Santoso (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The thesis discusses about “The Influence of Competency and Self-Efficacy on Nurse Career Development in National Cancer Center of “Dharmais” Cancer Hospital Jakarta, with the background ofthe low percentage of nurses who conducting career development activity in orientation nurse level competency. The aim of this study is to find out the magnitude of the influence of competency and self-efficacy on nurse career development di National Cancer Center of “Dharmais” Cancer Hospital Jakarta. The method used in this study is quantitative method, using a sample of 90 respondents of orientation nurse and its sampling technique using saturation sampling. Based on the results of the research, it shows that the effect of Competence (X1) on Career Development (Y) is partially 18.7%, the effect of Self-Efficacy (X2) on Career Development (Y) is partially 35.4% and the Effect of Competence (X1) and Self- Efficacy (X2) simultaneously have an effect on career development (Y), in the amount of 47.9%.